Edukasi Metode Servant Leadership untuk Meningkatkan Discharge planning oleh Perawat di Rumah Sakit: Education on Servant Leadership Methods to Improve Discharge Planning by Nurses in Hospitals - Batewa, Erny; Dian Ellina, Agusta (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Discharge planning is an essential process that starts at patient admission and continues through discharge to ensure continuity of care and safety. However, in many healthcare settings, it is often underperformed, limited to providing basic discharge instructions like follow-up schedules. This inadequate approach fails to address patients’ comprehensive needs for at-home care, leading to gaps in post-discharge care and safety. To address this issue, this community service initiative aimed to enhance the quality of discharge planning performed by nurses through education on the Servant Leadership Method, focusing on fostering patient-centered care and empowering healthcare teams. The program was conducted from February 1 to February 10, 2024, at RSUD Banggai Regency. It involved three main phases: preparation, implementation, and evaluation. The preparation phase included developing educational materials and coordinating with hospital management. During the implementation phase, nurses attended workshops, discussions, and simulations focusing on servant leadership principles such as empathy, communication, and patient empowerment. The evaluation phase involved pre- and post-training assessments using structured tools to measure changes in discharge planning practices. The results showed a significant improvement in discharge planning quality after the education program. Nurses demonstrated enhanced understanding and application of servant leadership principles, leading to more comprehensive discharge instructions and better coordination for follow-up care. Patients reported improved clarity regarding their care plans, and nurses expressed greater confidence in implementing discharge procedures. Education on the Servant Leadership Method effectively improved discharge planning practices among nurses at RSUD Banggai. By focusing on empathy and teamwork, this approach enhanced patient-centered care and continuity of care. Further application of this method in broader nursing practices could yield additional benefits for healthcare delivery and patient outcomes.